Long COVID and oral health: are we ready? - Rodríguez Cárdenas, Yalil Augusto (2022)
According to recent epidemiological reports, the pandemic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is close to disappearing or, at least, we will have to live with it in an endemic form, due, in part, to the immunity generated by vaccines and, on the other hand, herd immunity. While this is happening, the world nervously awaits the appearance of new variants or zoonotic diseases, such as the recent monkeypox.